Hardenable casting material for producing molded plastic parts

By adding less than 1% by weight of expandable micro-units and granular mineral particles to the hardenable castable material, the problem of difficult cleaning of the surface of the molded plastic parts is solved, and the effect of significantly improving cleanability and shortening the cleaning cycle is achieved.

CN119463281APending Publication Date: 2025-02-18BLANCO GMBH & CO KG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311369178.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-04-11
Filing Date
2020-02-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing hardened castable materials used to produce molded plastic parts are difficult to clean on the surface, resulting in poor cleanability.

Method used

The filler material composition is formed by adding less than 1% by weight of expandable microunits to the hardenable castable material and combining particulate mineral particles to form a filler material composition to improve the surface cleanability of the molded plastic parts.

Benefits of technology

The surface cleanability of molded plastic parts is significantly improved, and the cleaning cycle is shortened, for example, by more than 25%, while retaining the visual appeal of the structured surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004506332250000051
    Figure BDA0004506332250000051
  • Figure BDA0004506332250000074
    Figure BDA0004506332250000074
Patent Text Reader

Abstract

The invention relates to a hardenable casting material for producing molded plastic parts, comprising a casting material containing a binder material composition and a filler material composition, the filler material composition having at least a first part of particulate mineral particles, and the filler material composition has a second portion of the expandable microunits of less than 1.0 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of February 17, 2020, an invention name of “Hardenable Casting Material for the Production of Molded Plastic Parts”, an international application number of PCT / DE2020 / 200012 and a Chinese national application number of 202080027653.2. Field of the Invention

[0002] The invention relates to a hardenable casting material for producing a molded plastic part, comprising a casting material having a binder material composition and a filler material composition, wherein the filler material composition comprises at least a portion of granular mineral particles.

[0003] The invention also relates to the use of the hardenable casting material.

[0004] Furthermore, the invention relates to a moulded plastic part produced using the hardenable casting material. Background Art

[0005] Hardenable casting materials are used for producing molded plastic parts, in particular in the sanitary or kitchen area, such as kitchen sinks, worktops, bathtubs, washbasins, etc. Hardenable casting materials usually contain binder materials and filler materials to increase the mechanical properties of the molded plastic parts, as is known, for example, from DE 3832351 or WO 2005-071000 A1.

[0006] However, such hardenable casting materials have the disadvantage that the surface of the molded plastic parts produced therefrom is difficult to clean and therefore has poor cleanability. For this purpose, it is known from EP 1 240 221 B1 to add a portion of a granular hydrophobic and / or oleophobic plastic material to the hardenable casting material. It is also known from EP 1 487 906 A1 to add a hydrophobic monomer component comprising at least one organosiloxane functionalized with unsaturated groups.

[0007] It is therefore an object of the present invention to provide an alternative casting material and molded plastic parts which are at least comparable in cleanability. Summary of the invention

[0008] The present invention achieves the above object by a hardenable casting material for producing molded plastic parts, which comprises a casting material having a binder material composition and a filler material composition, wherein the filler material composition comprises at least a portion of granular mineral particles and the filler material composition comprises a second portion of expandable microunits less than 1 weight %.

[0009] The invention also achieves the object by the use of a hardenable casting material according to any of the embodiments 1 to 12 below for producing molded plastic parts for use in the kitchen and / or sanitary area, in particular for kitchen sinks and kitchen worktops.

[0010] The invention also achieves the object by the use of a molded plastic part produced using a hardenable casting material according to any of the embodiments 1 to 12 below.

[0011] One of the advantages achieved thereby is that the cleanability of the surface of the molded plastic part can be improved: by using a very low concentration of expandable microcells, it was surprisingly determined that the cleaning work can be improved in the case of standardized test contamination. In other words, a reduction of the cleaning cycles required to reach a specific degree of contamination can be achieved, for example by more than 25%, compared to a material sample without expandable microcells. The content of granular mineral particles in the hardenable casting material ensures that molded plastic parts made therefrom can be obtained which have a structured surface, for example a decorative granite surface. In this way, despite the use of expandable microcells in the hardenable casting material, the structuring of the surface is essentially retained, so that the visual appeal associated with the structuring, for example the similarity of the decorative granite surface to natural granite, is largely retained.

[0012] Other features, advantages, and embodiments of the invention are described below or are disclosed therein. Specific implementation plan

[0013] According to one embodiment, the second portion is less than 0.5 wt %, in particular less than 0.25 wt %, preferably less than 0.175 wt % and / or at least 0.10 wt %, preferably at least 0.15 wt %.This reduces the costs of providing the hardenable casting material without deteriorating its cleanability.

[0014] According to another embodiment, the expandable microcells are designed to be thermoplastic. This has the advantage that it is possible to carry out the expansion of the microcells in a simple manner during the production of the molded plastic part based on temperature dependence, in particular by heating.

[0015] According to another embodiment, the expandable microcells are designed to be spherical. Due to the spherical shape, uniform expansion and uniform distribution of the microcells in the hardenable casting material are possible.

[0016] According to another embodiment, the average diameter of the spherical microelements is from 10 μm to 30 μm, preferably from 15 μm to 25 μm. This makes it possible to further improve the cleanability without impairing the visible structuring of the surface.

[0017] According to another embodiment, the average density of the expandable microcells is less than 30 kg / m3, in particular less than 20 kg / m3, preferably less than 15 kg / m3, in particular less than 10 kg / m3. After the hardenable casting material is transferred into a mold for producing a molded plastic part, the microcells with such a density remain substantially uniformly distributed in the hardenable casting material (whose binder generally has a greater density). In other words, it is possible to simply produce a molded plastic part with the hardenable casting material.

[0018] According to another embodiment, the expandable microcell comprises a closed cavity volume of at least 20%, preferably at least 30%, in particular at least 50% of the total volume of the microcell, thereby ensuring sufficient expandability of the microcell.

[0019] According to another embodiment, the binder material composition comprises at least a portion of a liquid monomer acrylate. This has the advantage that in the production of molded plastic parts, the liquid monomer acrylate can be polymerized to a polyacrylate by hardening. In order to increase the viscosity of the hardenable casting material, a portion of the prepolymerized acrylate component can be added to the monomer acrylate, for example, prepolymerized polymethyl methacrylate PMMA can be added to the monomer methyl acrylate.

[0020] According to another embodiment, the material of the mineral particles comprises a composition based on silicate and / or aluminum hydroxide. For example, the silicate filler material may include glass, quartz, cristobalite, etc. The filler material based on aluminum hydroxide may include, for example, aluminum trihydrate.

[0021] According to another embodiment, the filler material composition comprises at least a portion of a peroxide mixture. This has the advantage that it makes possible a simple control of the polymerization in the production of molded plastic parts.

[0022] According to another embodiment, the hardenable casting material comprises at least two different granular mineral particles. This has the advantage of increased flexibility in the design of the structured surface.

[0023] According to another embodiment, the ratio of the weight proportion of expandable microelements to the weight proportion of at least one of the at least two different granular particles is less than 10%, in particular less than 5%, preferably between 2% and 3%.

[0024] This achieves a significant increase in the cleanability of the surface of the molded plastic part without having to change the basic properties of the basic composition of the hardenable casting material and thus without having to modify the production process in a costly manner for suitability.

[0025] Further important features and advantages of the invention result from the dependent embodiments and the following description.

[0026] It is understood that the above-mentioned features as well as features not yet described can be used not only in the respectively indicated combination but also in other combinations or alone, without departing from the invention.

[0027] Preferred designs and embodiments of the present invention are further described in the following description.

[0028] It was found that by using expandable microelements according to the invention, in particular expandable microspheres, it is possible to improve the cleanability of surfaces, in particular the cleanability of the visible side of molded plastic parts.

[0029] Comparative Example 1

[0030] A hardenable casting material is prepared, wherein a binder material is added to the filler material. The binder material is obtained by dissolving PMMA in MMA so that the binder material contains 19% by weight of PMMA and 81% by weight of MMA. In addition, stearic acid and trimethylolpropane trimethacrylate (TRIM) are added as crosslinking agents.

[0031] Filler materials include different types of granular quartz materials (Gebrüder Dorfner GmbH & Co., Hirschau) and wollastonite (Wollastonite) (Quarzwerke, Frechen). The following types of And wollastonite:

[0032] Earthy brown 4 / 8 (average particle size 570 microns)

[0033] White 1 / 8 (average particle size 570 microns)

[0034] White 2 / 9 (average particle size 330 microns)

[0035] Wollastonite (average needle length 1 to 25 microns)

[0036] By using different Type, visually attractive decorative granites can be achieved. The addition of wollastonite improves the mechanical properties of molded plastic parts that can be produced with the hardenable casting material and in particular reduces the occurrence of so-called blistering on the molded parts, which can occur due to local overheating during the hardening process. The advantages of using wollastonite are described in EP 1207180 A1, which is hereby incorporated by explicit reference.

[0037] Filler material is added to binder material now, and evenly mixed with it.Further peroxide mixture is joined in hardenable casting material to slow down polymerization and make casting material harden.Such peroxide mixture can for example comprise peroxydicarbonate di-(4-tert-butylcyclohexyl) ester and / or dilauroyl peroxide.Alternatively or additionally, binding agent comprises one or more crosslinking agents.Possible crosslinking agent can be for example selected from the material in following group: aliphatic or aromatic difunctional, trifunctional or multifunctional acrylate or methacrylate, and / or epoxy acrylate or methacrylate, and / or aliphatic or aromatic difunctional, trifunctional or multifunctional urethane acrylate or methacrylate, and / or difunctional, trifunctional or multifunctional polyester acrylate or methacrylate, and / or difunctional, trifunctional or multifunctional silicon acrylate or methacrylate, silicon urethane acrylate or methacrylate and silicon polyester acrylate or methacrylate, or their combination.

[0038] The composition of the hardenable casting material according to Comparative Example 1 is shown in the following Table 1, wherein the content of each component is expressed in % by weight.

[0039] Table 1

[0040]

[0041] The peroxide mixture consists essentially of a mixture of dilauroyl peroxide and di-(4-tert-butylcyclohexyl) peroxydicarbonate in a weight ratio of 1.5:1.

[0042] The hardenable casting material is now placed in the kitchen sink casting mold and polymerized using heat.

[0043] The visible side of the test specimens taken from the kitchen sink thus obtained (hereinafter referred to as test specimens) were now subjected to defined soiling and defined cleaning: with regard to the evaluation of the cleanability or in other words the evaluation of the tendency of the molded plastic parts to become soiled, a synthetic model soil was used and the cleaning of this soil was carried out under defined conditions.

[0044] The following composition was used as a model pollutant:

[0045] 7 wt% Extra Black 4, soot (Degussa AG)

[0046] 40 wt% Processing oil 310 (ESSO AG)

[0047] 17 wt% Tricaprylin (Fluka, product number: 91040)

[0048] 36 wt% gasoline, Kp.65 / 100°C (Fluka, product number: 12270)

[0049] Specifically, the experiment was conducted as follows:

[0050] Prepare:

[0051] Before application, the test contaminant was stirred for about 1 hour using a magnetic stirrer. A new, flat brush was used, which had to be saturated with the test contaminant in advance. After a new test contaminant was produced, a new brush was also used in particular. This saturation of the brush was carried out in the following manner: a predetermined amount of the test contaminant was brushed on the film and allowed to act for 1 hour. The scrubbing side was cut from a sponge with a knife and cut into a circle with a diameter of about 8 cm from the soft side. After each individual cleaning attempt was completed, a new sponge was used and prepared as described above.

[0052] Implementation:

[0053] After the sample is prepared, 5 drops of the test contaminant are placed on the watch glass and a brush saturated with the test contaminant is brushed crosswise over the middle of the sample so that a square area with a side length of about 4 cm is covered. The sample is then stored in a drying cabinet at 40° C. for 15 min and then immediately rinsed with hot water at a temperature of about 65° C.-70° C. at a working angle of about 80° until the test contaminant is no longer recognizable and rinsed off, the hot water coming from a hose running near the sample surface (i.e. at a distance of about 10 cm) with an increased pressure, in particular a pressurization generated by manually squeezing the hoses together.

[0054] The specimens were then rinsed with high purity water. Afterwards, cleaning was performed in a cleaning device with a Scotch-Brite brand washing sponge, the scrubbing side of which was previously cut off. The sponge block cut for the cleaning device was oriented with the cut area towards the specimen, fastened to a rotatable plastic disc with double-sided tape, and moistened with approximately 5 ml of a 5% pre-stirred VISS detergent suspension.

[0055] In addition, 1 ml of a 5% VISS detergent suspension is placed on the specimen to be cleaned and then the sponge holder of the cleaning device is loaded with 2 kg, which is controlled or monitored by a scale arranged below the specimen, which is arranged on a laboratory lift. After 10 rotations per round at a rotation speed of 60 rpm, the cleaning state is visually checked after wiping the cleaning residues with a soft cloth. If the test or soot contamination has not been completely cleaned, 1 ml of a 5% detergent suspension is applied again and the next 10 cleaning cycles are carried out until there is no longer any test contamination located or recognizable on the specimen visually. The experiment is terminated after a maximum of 100 rotations.

[0056] Based on the previously described test method, the following results were obtained as a function of the number of revolutions required until complete cleaning of the test contaminant:

[0057] According to the comparative example (no ) Number of revolutions required (average from 8 separate tests): 31.25

[0058] Example 1

[0059] A casting material according to the invention was prepared which corresponded in its composition to a large extent to the hardenable casting material according to comparative example 1, with a certain amount of expandable microspheres (Akzo Nobel NV) being added. ) to exchange the corresponding amount of wollastonite. The rest of the material remains the same. In the casting material obtained in this way, Types of expandable microcells and wollastonite formed the first part of the filler material and expandable microcells formed the second part. The following types of expandable microcells were used:

[0060] 043DU80 (average diameter d50: 16-24 microns, specific density ≤ 10kg / m 3 )

[0061] The wall thickness of the expandable microcells is approximately 2 micrometers. The diameter of the microcells can expand by more than a factor of 3 due to temperature effects, wherein the wall thickness is then reduced by a factor of 20. The interior of the microcells contains hydrocarbons.

[0062] The composition of the hardenable casting material according to Example 1 is shown in the following Table 2, wherein the content of each component is expressed in % by weight, each relative to 100 kg of the hardenable casting material:

[0063] Table 2

[0064]

[0065] The peroxide mixture consists essentially of a mixture of dilauroyl peroxide and di-(4-tert-butylcyclohexyl) peroxydicarbonate in a weight ratio of 1.5:1.

[0066] As described for the hardenable casting material according to the comparative example, a kitchen sink was produced with the hardenable casting material according to example 1 and a test sample was then taken from the kitchen sink. Now, using the above preparation and by means of the above cleaning device, the visible side of the test sample taken from the kitchen sink thus obtained was subjected to defined soiling and defined cleaning.

[0067] Based on the previously described test method, the following results were obtained as a function of the number of revolutions required until complete cleaning of the test contaminant:

[0068] According to embodiment 1 of the present invention (having ) Number of revolutions required (average from 8 separate tests): 22.50

[0069] The results show that the addition of expandable microcells results in a significant reduction in the required cleaning cycle, in particular to a factor of 1.3, wherein in the above comparison, a reduction of a factor of 31.25 / 22.50=1.39 is achieved. Compared to the hardenable casting material obtained in the comparative example, the kitchen sink produced with the hardenable casting material according to one embodiment of the present invention has no visible damage to its decorative granite.

[0070] The use of expandable microelements according to the invention thus results in an improved cleanability of the surface.

[0071] In summary, at least one of the embodiments of the present invention has at least one of the following advantages:

[0072] Improved cleanability of the surface of molded plastic parts

[0073] Very small amounts of required effective additives and thus lower costs combined with significantly improved cleanability

[0074] High flexibility in the optical design of the surface

[0075] The present invention provides the following embodiments.

[0076] Embodiment 1: Hardenable casting material for producing molded plastic parts,

[0077] The hardenable casting material comprises a casting material having a binder material composition and a filler material composition, wherein the filler material composition comprises at least a portion of granular mineral particles,

[0078] It is characterized in that

[0079] The filler material composition comprises less than 1.0% by weight of the second portion of expandable microelements.

[0080] Embodiment 2: The hardenable casting material according to embodiment 1 is characterized in that the second portion is less than 0.5 weight %, in particular less than 0.25 weight %, preferably less than 0.175 weight % and / or at least 0.10 weight %, preferably at least 0.15 weight %.

[0081] Embodiment 3: The hardenable casting material according to any one of embodiments 1-2, characterized in that the expandable microunits are designed to be thermoplastic.

[0082] Embodiment 4: The hardenable casting material according to any one of embodiments 1 to 3, characterized in that the expandable microunits are designed to be spherical.

[0083] Embodiment 5: The hardenable casting material according to embodiment 4 is characterized in that the average diameter of the spherical microunits is between 10 micrometers and 30 micrometers, preferably between 15 micrometers and 25 micrometers.

[0084] Embodiment 6: The hardenable casting material according to any one of embodiments 1 to 5, characterized in that the average density of the expandable microunits is less than 30 kg / m 3 , especially less than 20kg / m 3 , preferably less than 15kg / m 3 , especially less than 10kg / m 3 .

[0085] Embodiment 7: The hardenable casting material according to any one of embodiments 1 to 6, characterized in that the expandable microcell comprises a closed cavity volume of at least 20%, preferably at least 30%, in particular at least 50% of the total volume of the microcell.

[0086] Embodiment 8: The hardenable casting material according to any one of Embodiments 1 to 7, characterized in that the binder material composition comprises at least a portion of a liquid monomer acrylate.

[0087] Embodiment 9: The hardenable casting material according to any one of embodiments 1 to 8, characterized in that the material of the mineral particles comprises a composition based on silicates and / or aluminum hydroxide.

[0088] Embodiment 10: The hardenable casting material according to any one of Embodiments 1-9, characterized in that the filler material composition comprises a third portion of a peroxide mixture.

[0089] Embodiment 11: The hardenable casting material according to any one of Embodiments 1-10, characterized in that the hardenable casting material contains at least two different granular mineral particles.

[0090] Embodiment 12: The hardenable casting material according to Embodiment 11 is characterized in that the ratio of the weight proportion of the expandable microunits to the weight proportion of at least one of the at least two different granular particles is less than 10%, in particular less than 5%, preferably 2% to 3%.

[0091] Embodiment 13: Use of the hardenable casting material according to any of embodiments 1 to 12 for producing molded plastic parts for use in the kitchen and / or sanitary area, in particular for kitchen sinks and kitchen worktops.

[0092] Embodiment 14: A molded plastic part produced using the hardenable casting material according to any one of Embodiments 1-12.

[0093] Although the present invention has been described using preferred embodiments, it is not limited thereto but can be modified in various ways.

Claims

1. Hardenable casting materials for the production of molded plastic parts, The hardenable casting material comprises a casting material having a binder material composition and a filler material composition, wherein the filler material composition comprises at least a portion of granular mineral particles, It is characterized in that The filler material composition comprises a second portion of expandable microelements, wherein the second portion is at least 0.10 wt % and less than 0.25 wt %, in The expandable microunit is designed to be spherical. The expandable microcell comprises a closed cavity volume of at least 20%, preferably at least 30%, in particular at least 50% of the total volume of the microcell, and The diameter of the microcell can expand more than 3 times.

2. The hardenable casting material according to claim 1, characterized in that The second portion is less than 0.175 wt % and at least 0.15 wt %.

3. The hardenable casting material according to any one of claims 1 to 2, characterized in that The expandable microcells are designed to be thermoplastic.

4. The hardenable casting material according to claim 1, characterized in that The average diameter of the spherical microunits is between 10 micrometers and 30 micrometers, preferably between 15 micrometers and 25 micrometers.

5. The hardenable casting material according to any one of claims 1 to 4, characterized in that The average density of the expandable microunits is less than 30 kg / m 3 , especially less than 20kg / m 3 , preferably less than 15kg / m 3 , especially less than 10kg / m 3 .

6. The hardenable casting material according to any one of claims 1 to 5, characterized in that The binder material composition comprises at least a portion of a liquid monomer acrylate.

7. The hardenable casting material according to any one of claims 1 to 6, characterized in that The material of the mineral particles comprises a composition based on silicates and / or aluminium hydroxide.

8. The hardenable casting material according to any one of claims 1 to 7, characterized in that The filler material composition comprises a third portion of a peroxide mixture.

9. The hardenable casting material according to any one of claims 1 to 8, characterized in that The hardenable casting material comprises at least two different granular mineral particles.

10. The hardenable casting material according to claim 9, characterized in that The ratio of the weight proportion of expandable microelements to the weight proportion of at least one of the at least two different granular particles is less than 10%, in particular less than 5%, preferably 2% to 3%.

11. Use of a hardenable casting material according to any one of claims 1 to 10 for producing molded plastic parts for use in the kitchen and / or sanitary area, in particular for kitchen sinks and kitchen worktops.

12. A moulded plastic part produced using the hardenable casting material according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • component, in particular built-in sink and method for its manufacture

    DE3832351A1

  • Curable casting composition

    EP1207180A1

  • Hardenable casting material and a plastic shaped body produced using said casting materials

    EP1240221B1

  • Casting compound and plastic shaped bodies produced therefrom

    EP1487906A1

  • Casting mass in particular for the production of kitchen sinks, moulded sanitaryware, kitchen worktops or similar

    WO2005071000A1